DETOXICATION OF BY-PRODUCTS OF OIL AND GAS INDUSTRY ACCOMPANIIED BY OBTAINING IRON AND SULFUR-CONTAINING BINDERS FOR STRUCTURAL BUILDING MATERIALS - okolova Julia Andreyevna; Akulova Marina Vladimirovna; Isakulov Baizak Razakovich; Sokolova A. G.; Kulsharov Berikbay Baltabayevich; Isakulov Abilkhair Baizakovich (Academic Scientific Journal of Chemistry, 2020)
In this paper, the authors considered the issues related to reducing negative impact of large-tonnage toxic industrial wastes on environment by means of their detoxication and application as effective binders for building materials. For implementation of scientific researches, the standard methods of analysis of physical and mechanical properties have been used for the stone based on iron and sulfur containing binders; the contemporary methods of differential and thermal, X-ray diffraction analysis, microscopic analysis and testing apparatuses have been used. While carrying out experimental research, the authors have realized a scientific hypothesis stating that for increasing the effect of additional activation for eact particles of iron- and sulfur containing additives, their comilling has been applied. As the result, there took place mutual neutralization and detoxication of solid industrial byproducts with opposite chemical properties. In the course of experimental work aimed at preliminary determination of composition and activation of sulfur-contating additives, wet grinding was done on the pebble mill by applying abrasive and impact forces. In the course of combined action of mechano-chemical activation of industrial byproducts, in the presence of water, accompanied by sulfur-containing raw mixtures for manufacturing of building materials, there was used the method of mutual neutralizion of chemically hazardous substances forming a part of industrial wastes. These methods enable to reduce the consumption of a binder due to its partial replacement by toxic by-products of oil and gas industry and metallurgy. The characteristics and properties of the specimens of iron and sulfur-containing binder have been studied at the age of 7, 14 and 28 days of air hardening. The specimens were exposed to thermal and steam curing. It was stated that air hardened iron and sulfur-containing binders at the age of 14 days have reached the ultimate compressive strength of 62.0 MPa, at the age of 28 days – 66.5 MPa, correspondingly. The same composition exposed to steam curing at the age of 28 days has compression strength of 74.5 MPa that attests to the fact that steam curing has a positive impact on gain in strength of iron and sulfurcontaining binder. The obtained research results could be apllied as an effective substance for manufacturing mortars and concrets in construction industry.